2022
DOI: 10.33029/0206-4952-2022-43-3-255-265
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation profi le and expression of TLR2, TLR9, IL4, IL13 genes in pediatric patients with atopic dermatitis

Abstract: РезюмеВведение. Атопический дерматит (АтД) принадлежит к группе многофакторных заболеваний, которые, как полагают, возникают в результате сложных взаимодействий между генетическими факторами и проявлениями окружающей среды. Объяснить, каким образом окружающая среда влияет на риск развития аллергии, можно, опираясь на понимание эпигенетических механизмов, участвующих в регуляции экспрессии генов.Цель исследования -проведение комплексного анализа механизмов иммунитета (метилом; экспрессионный профиль генов TLR2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Increased levels of all suggested molecules may be an evidence of Th2 immune response enhancement in the acute phase of the dermatitis, which is, in fact, an acknowledged classic model of the systemic AD pathogenesis. Nevertheless, our previous studies showed that at the same time there might be a difference at the local level (in the skin), where the inflammation takes place and anti-inflammatory mechanisms prevail [2]. Targeted expression analysis revealed that in the skin samples the expression of TLR9 and IL4 was 12 times significantly lower (p < 0.0001, p < 0.0005) in the lesional skin; and there was a 6-fold decrease in case of TLR2 (p < 0.01).…”
Section: Resultsmentioning
confidence: 94%
“…Increased levels of all suggested molecules may be an evidence of Th2 immune response enhancement in the acute phase of the dermatitis, which is, in fact, an acknowledged classic model of the systemic AD pathogenesis. Nevertheless, our previous studies showed that at the same time there might be a difference at the local level (in the skin), where the inflammation takes place and anti-inflammatory mechanisms prevail [2]. Targeted expression analysis revealed that in the skin samples the expression of TLR9 and IL4 was 12 times significantly lower (p < 0.0001, p < 0.0005) in the lesional skin; and there was a 6-fold decrease in case of TLR2 (p < 0.01).…”
Section: Resultsmentioning
confidence: 94%